Performing Deference in Ahiqar The significance of a Politics of Resistance in the Narrative and Proverbs of Ahiqar - Southwood, Katherine 1982- (2021)
This article argues that subtle resistance to power was all-important in Ahiqar and this was highlighted through interpreting the narrative and poetic sections symbiotically. This resistance to power, however, was hidden in Ahiqar, embedded in ironic twists on traditionally expected roles, and in the display of obedience, deference, and loyalty that is performed in the face of the king’s power. The article suggested that Ahiqar was performed to audiences at Elephantine and that a potential way for Elephantine audiences to interpret Ahiqar was in light of Persian dominance.